ENSO-Related variability of the southern hemisphere winter storm track over the eastern Pacific–Atlantic sector - Solman, Silvina Alicia; Menendez, Claudio Guillermo
The interannual variability associated with the ENSO of winter storm tracks over the region extending from the eastern South Pacific Ocean across South America to the South Atlantic Ocean is described using 39 yr of data from the NCEP reanalysis data base. Tropical sea surface temperature anomalies associated with ENSO induce large-scale atmospheric circulation anomalies over large areas of the Southern Hemisphere. In particular, positive height anomalies dominate the Bellingshausen Sea during warm events, and consistently, a weakening of the eddy activity at low levels is found to the west of the Antarctic Peninsula. During El Nin˜o (EN) the storm track evidences an equatorward shift over the subtropical Pacific Ocean and a slight strengthening in the central Atlantic Ocean. Time-lagged correlation analysis applied to anomalies of the 300-hPa meridional wind at selected base points was used to study the structure and propagation characteristics of the waves. During EN, waves emanating from the Atlantic–Indian Ocean storm tracks tend to propagate preferably along the subpolar branch of the Pacific Ocean storm track near Australia. Over the subtropical Pacific Ocean the wave train propagates along a northern path compared with cold events consistent with an equatorward shift of the axis of maximum baroclinicity. Additionally, large eddy activity at lower levels but weak eddy activity at upper levels were found for that region. During La Nin˜a (LN), wave packets propagate more coherently along the subtropical branch of the storm track over the South Pacific Ocean, attaining larger amplitudes at upper levels and developing over broader latitudes compared to the warm phase. A poleward deflection of subtropical waves and northeastward deflection of subpolar waves are also found for LN. Waves propagating through the Atlantic Ocean storm track evolve from the subtropical branch of the Pacific Ocean storm track for LN winters and from both the subtropical jet and the subpolar latitudes for EN. Time-lagged correlation ...